Coach Turnover in Top Professional Brazilian Football Championship: A Multilevel Survival Analysis - Tozetto, Alexandre B.; Carvalho, Humberto M.; Rosa, Rodolfo S.; Mendes, Felipe G.; Silva, Walan R.; Nascimento, Juarez V.; Milistetd, Michel (Frontiers in Psychology, 2019)
In this study we examined the probability of coaches´ survival in the top Brazilian professional football championship considering variation across the competitive seasons between 2012 and 2017, considering a multilevel framework. We also considered whether previous coaching experience in the top Brazilian professional football championship would change the probability of coaches´ survival across the season. The data considered 4,560 games from the top professional Brazilian football league (Campeonato Brasileiro Série A) between the 2012 and 2017 seasons. In each season, the coach from each team at the start of the season was followed, being recorded the round were the event occurred, i.e., the coach being sacked. A total of survival of 120 coaches was considered between the seasons of 2012 and 2017, i.e. 20 coaches at the beginning of each season. Coaches were assigned as novice (no previous experience as head coach in the top Brazilian championship) or experienced (with at least a previous experience as head coach in the top Brazilian championship). Data was available and extracted from the official website of the Brazilian Football Confederation (https://cbf.com.br/). On average and considering un-pooled observations, the median life of a coach was about 16.5 rounds. Considering variation between 2012 to 2017 seasons, only about 26.3% (95% CI 18.2 to 36.1%) of the coaches ended a season without being sacked. By mid-season, at round 19, the probability of coaches´ survival was 0.42 (95% CI 0.32 to 0.53). Variation between season on survival estimates per round was substantial (between season standard deviation = 0.48, 95 % credible intervals 0.25 to 0.95; corresponding to an inverse logit = 0.62, 95% CI 0.56 to 0.72). There was no substantial variation between novice and experienced coaches´ survival probability. The present results expose the vulnerability of the coaching context in Brazilian football, potentially highlighting an excessive emphasis on short-term results to mediate club management decisions.